(untitled) (World Bulletin of Management and Law, 2023)
The article analyzes the following main directions of legal regulation of the participation of national minorities in political life: the system of granting advantages when participating in elections, quotas of seats in parliament, the establishment of proportions of representation of various ethnic groups in parliament, voting in parliament taking into account the opinions of ethnic groups, the adoption of special legislative acts aimed at protecting the rights of representatives of national minorities, establishment of institutions of commissioners for the rights of national minorities, granting special privileges to autonomies, giving compatriots the opportunity to participate in elections, supporting national diasporas abroad.